Radiation recall dermatitis induced by Amol during tamoxifen therapy – case report - Obtułowicz, Aleksander; Pirowska, Magdalena; Kosiniak-Kamysz, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2011)
In the course of radiation therapy different types of adverse reactions of the skin are observed in approximately 95% of patients. Among the various complications encountered after radiotherapy, radiation recall dermatitis (RRD) deserves special attention. Radiation dermatitis is a form of delayed hypersensitivity of irradiated skin, and the direct trigger factors are medicines – most chemotherapeutics. The reaction is an inflammatory dermatosis. It is limited to previously irradiated skin and appears a number of months after radiotherapy. The aetiology of RRD is still unclear. Its clinical presentation may vary from mild erythema to necrosis and ulceration. The article presents the case of a 50-year-old patient, who after radiotherapy for breast cancer, during the hormonal therapy (tamoxifen), developed RRD type skin reactions after skin application of Amol. The article presents a detailed differential diagnosis of skin changes of RRD type, and discusses the principles of treatment and prevention.